Peculiarities of the special knowledge application in the investigation of taking a government official or law enforcement officer as hostage (Law and Safety, 2023)
An effective investigation of any criminal offence is not possible without the use of specialised knowledge. Taking a government official or law enforcement officer as a hostage is no exception; on the contrary, from the moment information about the seizure is received, there is a need to engage specialists from various fields of knowledge, including a forensic expert, dog handler, explosives expert, etc.The purpose of the study is to investigate the scientific findings on the definition of the concept of “special knowledge” and to clarify its role in the investigation of criminal proceedings under Article 349 “Taking a government official or law enforcement officer as a hostage” of the Criminal Code of Ukraine. To achieve this goal, the study used the following methods: analysis, synthesis, comparison, critical thinking, and systemic and structural methods, with the aim of conducting a thorough study of theoretical developments, results of investigative and judicial practice, systematising the results and formulating conclusions.It has been argued that one of the ways to improve the efficiency of detection and investigation of crimes is to use specialised knowledge in the activities of law enforcement agencies. In particular, when investigating the taking of a government official or a law enforcement officer as a hostage, special knowledge should be considered as skills and abilities in a particular area which are used in criminal proceedings and contribute to establishing the truth in the case, which contributes to the effective completion of the investigation.As a result of the study, the special knowledge has been classified, namely: by the procedural position of the person who uses it, by the form of expression, by the need to use special knowledge at a certain stage of investigation, by the form of the final result, by the field of knowledge, by the degree of secrecy, by the purpose of use, by the significance of the results obtained.According to the results of a comprehensive analysis, three forms of special knowledge application are proposed in the course of investigation of taking a government official or law enforcement officer as a hostage: specialist involvement in investigative (detective) actions, appointment of forensic examinations and consulting.The role of specialists when involved in conducting typical investigative (detective) actions, such as: inspection of the scene, interrogation and investigative experiment, has been described. An indicative list of specialists who can assist an investigator has been proposed, and the tasks which can be solved through such interaction have been outlined. An indicative list of tasks facilitated by the appointment of forensic examinations has been provided.
Keywords: criminal proceedings; pre-trial investigation; forensic methodology; hostage-taking; government official; law enforcement officer; special knowledge; forensic methodology.